2021
DOI: 10.3390/fib9050029
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance Enhancement of RC Columns Using Thin High-Strength RC Jackets and CFRP Jackets

Abstract: The existing non-ductile RC structures built prior to the 1960s–1970s were mainly conceived to carry only vertical loads. As a result, the columns of these structures demonstrate poor overall hysteresis behavior during strong earthquakes, dominated by brittle shear or/and premature excessive slipping of the inadequately lap-spliced reinforcement. In the present study, the effectiveness of two different strengthening systems (including either the wrapping of the columns by carbon-fiber-reinforced polymer textil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Moreover, Kalogeropoulos and Tsonos [18][19][20] recently proposed a modified version of the analytical model which allows for the prediction of the seismic behavior of RC columns by controlling the adequacy of the length of lap-spliced reinforcement. The modified formulation is also used to precisely determine the necessary confinement to be provided by the strengthening material to prevent premature lap splice failure and allow for the yielding of reinforcement and the development of the column's nominal flexural moment capacity.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Kalogeropoulos and Tsonos [18][19][20] recently proposed a modified version of the analytical model which allows for the prediction of the seismic behavior of RC columns by controlling the adequacy of the length of lap-spliced reinforcement. The modified formulation is also used to precisely determine the necessary confinement to be provided by the strengthening material to prevent premature lap splice failure and allow for the yielding of reinforcement and the development of the column's nominal flexural moment capacity.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Kalogeropoulos and Tsonos experimentally investigated the seismic performance of original column subassemblages typical of substandard RC buildings built prior to the 1960-1970s with deficient lap splices, as well as the behavior of similar specimens retrofitted using thin steel jackets, RC jackets and CFRP jackets. They also proposed an analytical formulation for calculating the necessary confinement to achieve yielding of the deficiently lap-spliced rebars [18][19][20]. Anagnostou et al [21] used a database with experimental results of 67 RC columns with lapspliced steel bars, strengthened externally with FRP jackets subjected to pseudo-seismic loading to investigate the predictive performance of EC8.3 [22] and KANEPE [23] in calculating VR and θu.…”
Section: Introductionmentioning
confidence: 99%
“…Research works emphasise the significant improvements in the seismic behaviour of RC sub assemblages by increasing the compressive zone deformation capacity, such as the use in beam-column joints of HPFRC-High Performance Fibre Reinforced Concrete-Dogan [25]; Ficher [26]; Parra-Montesinos [27]; Shannag [28,29]; Konstantinos [30]; Chalioris [31,32]; Kalogeropoulos [33]; Bencardino [34]; Fares [35]. Muhaj (2020) [36] presented an experimental study of seismically reinforced concrete beams strengthened with post-tensioning with anchorages by bonding, which presented reduced residual deformation and anenhanced load capacity.…”
Section: Significant Research Studiesmentioning
confidence: 99%
“…Hosseini [11] found that the presence of FRP anchors provides extra ductility. Kalogeropoulos [12] and Kalogeropoulos and Tsonos [13] used steel fibers and thin RC jackets, in addition to FRP, for jacketing of the column. Different researchers have used different test methods for the shear test [14][15][16].…”
Section: Introductionmentioning
confidence: 99%